Enhancing Employee Performance Through Knowledge Management, Innovation Capabilities, Learning Organization, And Empowerment: an Empirical Study of The West Papua Provincial BPD - L. Herin, Theodorus; Mattalatta, Mattalatta; Bata Ilyas, Jamaluddin; Naninsih, Nur (Devotion : Journal of Research and Community Service, 2025)
This study aims to examine the influence between knowledge management, innovation capability, learning organization, employee empowerment and employee performance. The approach used in this study is a quantitative approach. The sample used in this study was employees of PT Bank Pembangunan Daerah West Papua Province which amounted to 155 respondents. The research data was obtained from the results of filling out the questionnaire and analyzed using SEM analysis techniques with the help of the SEM PLS program. The results show that (1) Knowledge management and innovation capability have a positive and significant effect on the learning organization, (2) Knowledge management and innovation capability have a positive and significant effect on employee empowerment, 3) Knowledge management has no positive and significant effect on employee performance, (4) Innovation capability has a positive and significant effect on employee performance; (5) Learning and empowerment organizations have a positive and significant effect on employee performance; (6) Knowledge management and innovation capabilities have an indirect effect on employee performance mediated by learning organizations and employee empowerment.